ANALISIS PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK (STUDI PADA KANTOR SAMSAT MEDAN UTARA) - Sitorus, Christina Mhirena; Rajagukguk, Jonson; Pasaribu, Jhonson (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze the application of good governance principles in improving the quality of public services at the North Medan Samsat office. Good governance is a concept that emphasizes the principles of participation, supremacy of law, transparency, responsiveness, special orientation, justice, effectiveness and efficiency, accountability and strategic vision in government management. Good quality of public services is very important to meet public expectations and increase public trust in the government. The research method used is descriptive qualitative with data collection techniques through interviews and documentation. This study involved North Medan Samsat employees and the community as service recipients. The results of the study indicate that the application of good governance principles at the North Medan Samsat Office has been carried out well. Transparency is realized through the provision of clear information related to service procedures, the principle of accountability is seen from the implementation of employee duties in accordance with standard operating procedures (SOP) and the existence of internal supervision. The supremacy of law is implemented with compliance with applicable regulations in the administrative process. Although the application of good governance principles has had a positive impact on public services, there are still several aspects that need to be improved, such as increasing the number of officers at the counter to speed up services and optimizing service technology. Thus, the implementation of the principle of good governance is more optimal, it is expected that the service at the North Medan Samsat Office will be increasingly qualified, effective and able to provide satisfaction to the community.